PENGARUH HAMBATAN SAMPING TERHADAP KINERJA RUAS JALAN LAMBUNG MANGKURAT DI PASAR RAHMAT KOTA SAMARINDA - ZAKIYAH, NURUZ (KURVA S JURNAL MAHASISWA, 2014)
The road is a place or area shaped track used as a means of transportation, both vehicles and pedestrians. Because of the way as infrastructure transport, it must be qualified in accordance with its function is to move goods or people from one place to another by means of a safe, comfortable, smooth, and economical.Gastric roads mangkurat a trade and shopping centers such as markets and shops and where had been impressed difficult to resolve parking problems especially in the know where the market usually makes creating congestion. The level of service that is unstable, in the sense that there are many obstacles on the road side, especially on the stomach mangkurat samarinda city, causing congestion.The method used to determine how a major influence on the performance bottleneck side road that is using methods MKJI 1997. And the research is to calculate the volume of traffic, the class barriers aside, and the degree of saturation at rush hour on this road. With the method in this research MKJI 1997. I did a survey for 4 days then it can be in the know the most traffic volume is highest on Thursday 21 may 2015 in the amount of 487 hours of 07:00 to 08:00 smp/clock to both directions. For the highest grade side barriers on Thursday 21 may 2015 in the amount of 531 hours of 07:00 to 08:00 for both directions then can code VH (very high) from these results. And to the highest degree of saturation occurred at 07:00 to 08:00 in the amount of 0.12 for both directions.2It can be concluded obstacle on the road beside the hull mangkurat ie by 25 %. Because it affects the performance of the hull mangkurat road. There fore to mitigate done to create some space in the location of alternative parking space located around market rahmat.